1985
DOI: 10.1152/jappl.1985.59.2.559
|View full text |Cite
|
Sign up to set email alerts
|

Plasma volume changes in middle-aged male and female subjects during marathon running

Abstract: Circulatory fluid shifts were studied in middle-aged runners (6 males and 5 females, ages 32-58 yr) during a 42.2-km marathon race run in mild weather (dry-bulb temperature = 17.5-20.4 degrees C). Running times for the subjects were 3:12-4:40 (mean values were 3:34 for males and 4:10 for females). Venous blood samples were taken without stasis in all subjects seated at rest before the start of the race and within 3 min of finishing; eight of the subjects also paused for samples at 6 and 27 km during the race. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 0 publications
2
18
0
Order By: Relevance
“…The women in this and other studies (Christensen and Ruhling, 1980;Myhre et al, 1985) also experienced a plateau in rectal temperature after ~30 min of exercise when drinking ad libitum. Montain and Coyle (1992) demonstrated that replacing ~80% of sweat losses in men was adequate to maintain a plateau in rectal temperature beyond ~1 h of strenuous exercise.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…The women in this and other studies (Christensen and Ruhling, 1980;Myhre et al, 1985) also experienced a plateau in rectal temperature after ~30 min of exercise when drinking ad libitum. Montain and Coyle (1992) demonstrated that replacing ~80% of sweat losses in men was adequate to maintain a plateau in rectal temperature beyond ~1 h of strenuous exercise.…”
Section: Discussionsupporting
confidence: 57%
“…The present ® ndings equate to intakes of 8± 13 ml´kg -1´h-1 (Table 1) without a single incidence of adverse gastrointestinal symptomatology. Fluid intakes were therefore generally higher than previously reported for female distance runners under similar conditions (Myhre et al, 1982(Myhre et al, , 1985Millard-Staþ ord et al, 1995). This may be the result of habitual entrained ¯uid intake practices of marathon runners who reside in warm climates, or possibly `dry mouth' (Greenleaf, 1992) resulting from the gas exchange measurements that immediately preceded the simulated ¯uid stations.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…Despite the relatively severe dehydration induced by the marathon in this study (5.5% weight loss), core temperature was maintained within expected range (36.6 -38.9 CC). This is consistent with previous studies (Pugh et al 1967;Maughan et al 1985;Myhre et al 1985;Noakes et al 1988). The rise in core temperature is directly related to the metabolic rate and thus running speed sustained during prolonged exercise (Maughan et al 1985;Noakes et al 1991a).…”
Section: Discussionsupporting
confidence: 94%